Treinamento da Compensação de Excitações de Voz Esparsas10.14209/jcis.2001.9 - Arjona Ramirez, Miguel (Journal of Communication and Information Systems, 2015)
Sparse excitation from fixed code hooks provides for efficient search algorithms and high-quality speech. However, as the bit rate decreases. sparsity causes hearing effects that may he phase-compensated. A procedure is described for training the impulse response of a phase compensation filter over a large database. Two four-pulse ACELP coders operating at 5.3 kbit/s have their compensation filters trained. One of the coders searches the fixed codebook with the focused search (FOCS) algorithm and the other one uses the joint position and amplitude search (JPAS) algorithm. Listening tests were performed involving both compensated and uncompensated versions of these coders at 5.3 kbit/s and the uncompensated version at 8 kbit/s. The lower rate coders provided with trained sparsity compensation are perceived to deliver speech quality equivalent to that achieved with 8 kbit/s coders. Additionally, the beneficial hearing effect is more pronounced with the computationally efficient JPAS. Further. truncation of the dispersion response prior to its training is shown to decrease the operational complexity of the search algorithm while enhancing the speech quality by a small amount.